THE IMPACT OF ENVIRONMENT AND BEHAVIOR OF DAILY CATTLE BREEDERS ON CONSIDERATION OF INVESTORS IN INVESTING IN GALENGDOWO VILLAGE, JOMBANG - J.E. Sutanto; Farida Pulansari; Srie Muljani; Sukirmayadi Sukirmayadi (International Journal of Economics, Business and Accounting Research (IJEBAR), 2022)
The purpose of the study was to determine and analyze whether cow dung, environmental permits, and farmer behavior affect investors in investing in Galengdowo village. Design/Methodology/approach, the population in this study were all dairy farmers who had more than 5 dairy cows, while the number of samples used was 73 respondents. Data collection in this study was carried out by distributing research instruments using a Likert scale instrument and after the data was collected, data processing was carried out using the SPSS version 25 program. towards investors; (2) the environmental permit variable partially has a significant effect on investors, and (3) the breeder's behavior variable partially has a significant effect on investors. Based on the multiple linear regression equation, it can be explained as follows: First, the cow dung waste variable (X1) has the highest influence. Second, the farmer behavior variable (X3) has the lowest effect compared to the cow dung waste variable (X1) and the environmental permit variable (X2).